OSH-Based School Building Safety Risk Evaluation through Workplace Environmental Measurements at MAN Islam Cendekiawan - Yayu Angriani; Idham Halid; Suyitno Suyitno; Rian Wahyul Ikhtiar; Uswatun Hasanah (Open Access Health Scientific Journal, 2026)
Background: School buildings are important educational facilities that must provide a safe, healthy, and comfortable environment to support learning activities. Inadequate management of workplace environmental conditions and building safety aspects may increase potential risks to students, teachers, and school staff. The implementation of Occupational Safety and Health (OSH) principles in school facilities is essential to identify hazards, prevent accidents, and improve safety management. This study aimed to evaluate school building safety based on OSH principles through workplace environmental measurements and assessment of safety conditions at MAN Islam Cendekiawa.Methods: This study used a descriptive quantitative design with an observational approach. Data were collected through direct measurements of workplace environmental parameters, including lighting intensity using a lux meter, temperature and humidity using a thermo-hygrometer, and noise levels using a sound level meter. Observations were also conducted to assess physical building conditions, ventilation systems, building maintenance, and safety facilities. The collected data were analyzed descriptively by comparing the measurement results with applicable Occupational Safety and Health (OSH) standards.Results: The results showed that workplace environmental conditions at MAN Islam Cendekiawa were generally adequate to support educational activities. Lighting intensity, temperature, humidity, and noise levels were within acceptable limits based on OSH requirements. However, several aspects, including ventilation optimization, routine building maintenance, and improvement of safety facilities, require further attention to minimize potential hazards and enhance school safety management.Conclusion: The evaluation of school building safety through workplace environmental measurements provides an effective preventive approach for identifying potential hazards and improving OSH implementation in educational facilities. Continuous monitoring, improvement of infrastructure, and strengthening of safety management systems are recommended to create a safer and healthier learning environment. This study contributes to the development of OSH practices in schools and supports efforts to protect the health and safety of students, teachers, and school personnel.